How power affects postdecisional attitude change: reducing dissonance when decisions do not match with own or others’ preferences - Zonghuo Yu; Zhenfei Yu; Hao Wu; Yan Wang; Niels J. Van Doesum; Eric Van Dijk (Social Influence)
Decisions with consequences for self and/or others do not always match the respective preferences. Following cognitive dissonance theory, one option to deal with such mismatches is to change one’s attitudes post-decision. Inducing a different focus on self or others, perceived power may moderate how and when this happens. We indeed found that high power induced more attitude change after mismatches with one’s own preferences, whereas low power led to more attitude change after mismatches with others’ preferences. Study 1 (N = 129) showed this effect in an interpersonal setting; Study 2 (N = 127) revealed a similar pattern in a group context. Study 3 (N = 184) offered an explanation by including self-affirmation of either warmth or competence values.